BTG2 suppresses renal cell carcinoma progression through N6-methyladenosine - Qi, Fuming; Liu, Wenlong; Tan, Bo; Zhang, Juan; Ma, Yan; Cao, Congcong; Ma, Fujun; Zhu, Bo; Yang, Jinhui; Liu, Xiaoyun (Frontiers in Oncology, 2022)
The biological functions of N6-methyladenosine (m6A) modification of mRNA have recently received a great deal of attention. In previous studies, m6A methylation modification has been shown to regulate mRNA fate and to be crucial for the progression and development of tumors. BTG2 (B-cell translocation gene 2) is a member of BTG/TOB anti-proliferative protein family. BTG2 could inhibit cell proliferation and migration and regulate the cell cycle progression. In this study, we confirm that BTG2 is frequently down-regulated in renal cell carcinoma (RCC) tissues and its low expression is associated with unfavorable prognosis and decreased m6A level. Moreover, we found that m6A methylation modifies the 5'UTR of BTG2 to promote its mRNA stability by binding to IGF2BP2. It has been shown that CRISPR/dCas13b-METLL3 can specifically increase BTG2 m6A modification to significantly increase its m6A and expression levels. Then m6A hypermethylation in BTG2 mRNA could dramatically inhibit RCC cells proliferation and migration, and induce cells apoptosis. Taken together, our data show that BTG2 functions as a tumor suppressor and is frequently silenced via m6A modification in RCC.